Pirtobrutinib in Covalent Bruton Tyrosine Kinase Inhibitor Pretreated Mantle-Cell Lymphoma - Wang, Michael L.; Jurczak, Wojciech; Zinzani, Pier Luigi; Eyre, Toby A.; Cheah, Chan Y.; Ujjani, Chaitra S.; Koh, Youngil; Izutsu, Koji; Gerson, James N.; Flinn, Ian; Tessoulin, Benoit; Alencar, Alvaro J.; et al. (Journal of Clinical Oncology, 2023)
PURPOSEPirtobrutinib is a highly selective, noncovalent (reversible) Bruton tyrosine kinase inhibitor (BTKi). We report the safety and efficacy of pirtobrutinib in patients with covalent Bruton tyrosine kinase inhibitor (cBTKi) pretreated mantle-cell lymphoma (MCL), a population with poor prognosis.METHODSPatients with cBTKi pretreated relapsed/refractory (R/R) MCL received pirtobrutinib monotherapy in a multicenter phase I/II trial (BRUIN; ClinicalTrials.gov identifier: NCT03740529). Efficacy was assessed in the first 90 consecutively enrolled patients who met criteria for inclusion in the primary efficacy cohort. The primary end point was overall response rate (ORR). Secondary end points included duration of response (DOR) and safety.RESULTSThe median patient age was 70 years (range, 46-87), the median prior lines of therapy was 3 (range, 1-8), 82.2% had discontinued a prior cBTKi because of disease progression, and 77.8% had intermediate- or high-risk simplified MCL International Prognostic Index score. The ORR was 57.8% (95% CI, 46.9 to 68.1), including 20.0% complete responses (n = 18). At a median follow-up of 12 months, the median DOR was 21.6 months (95% CI, 7.5 to not reached). The 6- and 12-month estimated DOR rates were 73.6% and 57.1%, respectively. In the MCL safety cohort (n = 164), the most common treatment-emergent adverse events (TEAEs) were fatigue (29.9%), diarrhea (21.3%), and dyspnea (16.5%). Grade ≥3 TEAEs of hemorrhage (3.7%) and atrial fibrillation/flutter (1.2%) were less common. Only 3% of patients discontinued pirtobrutinib because of a treatment-related adverse event.CONCLUSIONPirtobrutinib is a first-in-class novel noncovalent (reversible) BTKi and the first BTKi of any kind to demonstrate durable efficacy after prior cBTKi therapy in heavily pretreated R/R MCL. Pirtobrutinib was well tolerated with low rates of treatment discontinuation because of toxicity.